Structural and ferroelectric properties of Pb1-xSrxTiO3 thin films - Pontes, F. M.; Leal, S. H.; Santos, MRMC; Leite, E. R.; Longo, Elson [UNESP]; Soledade, LEB; Chiquito, A. J.; Machado, MAC; Varela, José Arana [UNESP] (Springer, 2005)
Strontium-modified lead titanate (PST) thin films with composition Pb1-xSrxTiO3 (0.10 < x &LE; 0.60) were grown on Pt/Ti/SiO2/Si substrates using a soft chemical process. The crystallization of the PST thin films was achieved by heat treatment at 600&DEG;C. The structural and microstructural modifications in the films were studied using X-ray diffraction (XRD) and atomic force microscopy, respectively. The XRD study shows that the lattice parameters of polycrystalline PST thin films calculated from X-ray data indicate a decrease in lattice tetragonality with the increase in strontium content in these films. This indicates a gradual change from tetragonal to cubic structure. By atomic force microscopy analysis, the average grain size of the thin films was systematically reduced with the increase in Sr content. The dielectric property of the thin films was found to be strongly dependent on the Sr concentration. With 60 at.% Sr content, a ferroelectric to paraelectric phase transition was observed at room temperature.